PENERAPAN SISTEM ZONASI DI SURABAYA DITINJAU DARI PERMENDIKBUD NO. 20 TAHUN 2019 - Situmorang, Marwan Bilton; Astuti, Pudji (Universitas Negeri Surabaya, 2021)
Admission of New Students (PPDB) is a first step for schools to improve the quality of education. The purpose of this research is to know and understand the implementation of Permendikbud No. 20 of 2019 concerning zoning in Surabaya. To know and understand any obstacles with the zoning system as stipulated in Permendikbud No. 20 of 2019 in Surabaya, and to find out and understand the impact of the zoning system in the Acceptance of New Students based on Permendikbud No. 20 of 2019 against students outside of zoning who have talent and intelligence in Surabaya. This type of research is a sociological juridical study with a historical approach. The results showed that the zoning system at SMA Komplek Surabaya had been applied since the regulation of the Ministry of Education and Culture was imposed. The existence of a zoning system has two positive and negative sides. Inhibiting factors include: urgent time, lack of parents' knowledge of prospective students related to zoning, lack of socialization and information to the public regarding the implementation of PPDB online. The impact of the zoning system on the admission of new students to students outside of zoning who have talent and intelligence in Surabaya is that they cannot be accepted because it is based on Permendikbud No. 20 In 2019, students who have talent and intelligence cannot enroll in the desired school because it is outside of zoning. Keywords: Admission of new students , zoning system